Peran dan Tanggung Jawab Notaris Terhadap Pendirian Sarana Apotek - Reza Fahrizal (LPPM Universitas Ekasakti Padang, 2023)
Clergyman of Wellbeing Guideline Number 14 of 2021 with respect to Principles for Business Exercises and Items in the Execution of Hazard Based Business Permitting in the Wellbeing Area, where it is a retail exchange business coordinator explicitly for meds in drug stores. The point of the composing is to decide the type of drug store business element as per organization regulation by utilizing a standardizing legitimate examination approach technique. In light of the consequences of exploration that has been done, it was found that drug store business entertainers can be people, where drug specialists themselves set up drug stores utilizing individual capital. Drug specialists as individual business entertainers are as per the type of business element called an exchanging organization, where all drug store tasks are directed and overseen by drug specialists. Drug store business entertainers can likewise be non-people, for example, establishments and cooperatives as capital proprietors who work together with drug specialists.